10 WAYS TO ENHANCE STUDENT MOTIVATION - Xamrayeva Madinabonu Alisher qizi; Musayeva Zebokhon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract(eng). Our enthusiasm for doing something is what we refer to as motivation. It is the motivation behind all actions. The reason(s) why someone acts or behaves in a certain way is called their motivation. It aids in goal-setting and achievement. Since the word "motivation" is derived from the Latin verb "movere," it can be said that it is what keeps us moving. In the educational setting; motivation aids kids and teenagers in concentrating on a major objective or result. It takes time, effort, and patience from teachers to increase students' love of learning. There are numerous ways to encourage students to learn new things and to demonstrate how much fun it is to do so. This article presents arguments regarding motivation and examines current research on the most effective 5 techniques to boost students' commitment to learning throughout the academic year.